Penerapan E-Commerce Dalam Meningkatkan Daya Saing Usaha - Siti Maryama (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2013)
The objectives of the study are to: (1) analyze any motives that drives entrepreneurs use e- commerce; (2) reviewing the benefits of e-commerce for entrepreneurs and; (3) analyze the barriers of entrepreneurs in implementing e-commerce. The result indicates that the motive of entrepreneurs in implementing e-commerce are accessing global markets 56%, promoting the product 63%, branding 56%, close to the customers 74%, helps communication quickly to customers 63% and satisfying the customers 56%. Beside, the benefits are satisfying the customers 74% and competitive advantage 81%. The barriers faced by entrepreneurs are the lack of human resources 40%, the high cost of 20%, licensing difficulties 20%, and business network 20% .